Uma experiência com as linguagens pictórica e fotográfica no ensino das Artes Visuais - ALVES, Maria do Socorro de A. (2020)
This article presents a pedagogical proposal to promote concrete contact with artistic expressions - Pictorial and Photographic - in the process of teaching Visual Arts, with references from the 19th century to the present time. In contact with this imagetic universe, the research aimed to create possibilities of theory-practical contextualization by students in the ways of doing, thinking and understanding "art" in the "Art" classes of the Federal Basic Education Institution "Caminho das Estrelas School" - ECE. The Line of Research is Theoretical-Methodological Approaches of Teaching Practices, with emphasis on the experimental methodological cutout of making pictorial and photographic art by the student, source of object of investigation through the pedagogical activities proposed. These authorial creative actions reflected the contextualization of their ways of seeing and understanding the world around them. It is a qualitative research, of descriptive nature, opting for the bibliographic method and participant action research. The objective was to experiment and analyze possibilities of pictorial and photographic practice as a meaningful artistic/educational action. The state of the art was based on the tripod of three fundamental theorists for the Teaching of Art in contemporary school: The researcher and art/educator Ana Mae Barbosa, who through her studies of the Triangular Approach, guided the educational proposal to the learner by making, appreciating and contextualizing, as a significant process for understanding the image; John Dewey, who brought the theoretical bases of art as experience, leading reflection through the creation of images produced in art classes; and Herbert Read, poet, historian and art critic who was responsible for the conceptual development of Education through Art in the second half of the twentieth century. The process of implementing the pedagogical proposal of the research started from actions such as lectures, photographic essays and workshops in digital photography, darkroom, canvas painting and pinhole photography, carried out by professionals in the area with the students participating in the project. The result of this research-action also originated an exhibition with the productions in painting and photography made by the students, based on the experiences lived with the pictorial and photographic artistic expressions opportunized to them.